Permasalahan Kesulitan Membaca Permulaan Di Sekolah Dasar - Hafidz Pradita; Fatkhia Nur Azizah; Sofia Nanda Saputri; Dina Puspita Anggraini; Sri suwartini (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The purpose of this research is to determine the nature and behavior of teachers in addressing the problems faced by students who have difficulty reading. From Kindergarten (TK) to higher education, students receive reading education through organized, methodical, and continuous classroom activities. Both internal variables (originating from within the student) and external variables (originating from outside the student), as well as aspects of the learning approach, have an impact on this. Documents or document studies serve as the data source for this research. The consideration of the classroom teacher is the basis for selecting the class topic. The study's findings show how complex the reading challenges faced by students are. Students' knowledge of letters (vowels and consonants), diphthongs, as well as the challenges of reading syllables and words.